The sales income analysis of agricultural cooperatives - Myagmarzul, N (Mongolian Journal of Agricultural Sciences, 2017)
This paper aim is to define impact factor of cooperative sales income and recommend ways to increase cooperative income. The hypotheses were: the Government subsidy on raw material is key income factor of cooperative total income and cooperative characteristic influence to the their income. The economic survey conducted to 176 rural cooperatives and research methods are by inductive, deductive, comparative analysis and regression analysis. The 40% of Mongolian cooperatives are agricultural cooperatives and half of them cooperatives with members 201-300. The Government subsidy on raw material procurement is main advantage of agricultural cooperatives and lack of financial source and climate and nature condition are main disadvantage of cooperatives. In the research result, cooperative activities are unsustain, however Mongolian Government approved and implemented programs and projects for cooperative development. The sales income of cooperatives depends on income from animal raw materials, mainly Government subsidy on wool and cashmere procurement by econometric analyses of using Stata program. The cooperative working age (experience) significant to the sales income, also. With diversification cooperative activities in the future and Government support on multi-income generation for cooperatives for cooperative development.